Cholinergic control of inflammation in cardiovascular diseases - Leib, Christoph; Katus, Hugo; Kaya, Ziya (Trends in cardiovascular medicine, 2013)
A neuroimmunological reflexive signaling pathway with potent anti-inflammatory capacity has been discovered recently. Within this so called cholinergi…